2007
DOI: 10.2337/db07-0707
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aspirin Dosing on Platelet Function in Diabetic and Nondiabetic Patients

Abstract: OBJECTIVE-Diabetic patients may have a higher prevalence of platelet aspirin resistance than nondiabetic patients. Our goal was to analyze platelet aspirin responsiveness to various aspirin doses in diabetic and nondiabetic patients. RESEARCH DESIGN AND METHODS-We examined the effect of aspirin (81, 162, and 325 mg/day for 4 weeks each) on platelet aspirin responsiveness in 120 stable outpatients (30 diabetic patients and 90 nondiabetic patients) with coronary artery disease (CAD) using light transmittance agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
5
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(131 citation statements)
references
References 26 publications
11
111
5
4
Order By: Relevance
“…This hypothesis, generated from pharmacologic evidence of a dose-response relationship between aspirin and antiplatelet activity in diabetic patients, 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis, generated from pharmacologic evidence of a dose-response relationship between aspirin and antiplatelet activity in diabetic patients, 28 …”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Although the exact mechanisms are not clear, a subgroup analysis of the Aspirin-Induced Platelet Effect (ASPECT) study demonstrated that diabetic patients exhibited a significantly lower rate of resistance when given >100 mg daily compared with a lower (and more commonly used) dose of 81 mg daily. 28,29 Moreover, Electronic supplementary material The online version of this article (doi:10.1007/s11606-011-1757-y) contains supplementary material, which is available to authorized users.…”
Section: -3mentioning
confidence: 99%
“…Obecnie zaleca się podawanie tego leku w dawce 75-162 mg raz na dobę, to jest według takiego samego schematu dawkowania, jak u osób bez cukrzycy [263,264]. Jednak podawanie małej dawki kwasu salicylowego raz na dobę może nie zapewnić całkowitego hamowania aktywności płytkowej COX-1 i czynności płytek zależnej od tromboksanu A2 [265][266][267], co jest prawdopodobnie spowodowane zwiększonym obrotem płytek w cukrzycy [268]. Dane na ten temat wskazują, że u osób z cukrzycą i CVD stosowanie ASA 2 razy dziennie może przynieść korzystne efekty w postaci ciągłej skuteczności [268,269].…”
Section: Kwas Acetylosalicylowyunclassified
“…(ten Berg, Gerritsen et al 2002) Because patients with diabetes exhibit a higher prevalence of aspirin resistance on standard aspirin doses (81 mg/day) and have significantly higher ADP-and collagen-induced platelet aggregation, 11-dehydro-TxB 2 levels and the aspirin resistance may be partially overcome by higher aspirin doses. (DiChiara, Bliden et al 2007) Laboratory and genetic inconsistency, as well as dose dependence, is seen when agonists other than arachidonic acid (the most specific in assessing aspirin resistance), such as ADP, collagen, and epinephrine, are used for in vitro assessment of platelet inhibition by aspirin. (McCabe, Harrison et al 2005;Assadian, Lax et al 2007;Gurbel, Bliden et al 2007).…”
Section: Managementmentioning
confidence: 99%